2021
DOI: 10.1101/2021.08.13.21261861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Healthcare presentations with self-harm and the association with COVID-19: an e-cohort whole-population-based study using individual-level linked routine electronic health records in Wales, UK, 2016 - March 2021

Abstract: Background Multi-setting population-based studies on healthcare service presentations with self-harm covering the first 12 months of the COVID-19 pandemic are yet to be published. Aims Ascertain changes across settings in healthcare service presentations with self-harm during Waves 1 and 2 of the COVID-19 pandemic. Method E-cohort study using individual-level linked routine healthcare data from Wales, UK, 2016-March 2021. We measured weekly proportion of self-harm contacts and people who self-harmed in contact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Four studies used healthcare records in the UK to compare expected versus observed primary and secondary care–recorded episodes of self-harm, and found reductions of between 26 and 44%. 6,7,30,32 Another study based in Sri Lanka found a 32% reduction in hospital presentations for self-poisoning compared with pre-pandemic numbers. However, these estimates included months no later than August 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies used healthcare records in the UK to compare expected versus observed primary and secondary care–recorded episodes of self-harm, and found reductions of between 26 and 44%. 6,7,30,32 Another study based in Sri Lanka found a 32% reduction in hospital presentations for self-poisoning compared with pre-pandemic numbers. However, these estimates included months no later than August 2020.…”
Section: Resultsmentioning
confidence: 99%
“…All six studies rated as high-moderate quality (including one preprint) found decreases in frequency of presentations during the early months of the pandemic, with reductions of between 17 and 56% reported. 6,7, [29][30][31][32] These studies were of primary and secondary care settings combined (four studies), emergency department presentations among ages 18-25 years (one study) and self-poisoning presentations to hospital (one study). Four studies used healthcare records in the UK to compare expected versus observed primary and secondary care-recorded episodes of self-harm, and found reductions of between 26 and 44%.…”
Section: Findings Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of clinical presentations for self-harm in Wales, posted as a preprint after the timeframe of our review, showed an association between SARS-CoV-2 infection and self-harm. 28 Specifically, a prior history of a self-harm presentation appeared to increase the risk of SARS-CoV-2 infection; in contrast, infection was not associated with subsequent self-harm. 28 Emerging evidence suggests that SARS-CoV-2 infection may have a bidirectional relationship with psychiatric illness with each being a risk factor for occurrence of the other.…”
Section: Discussionmentioning
confidence: 95%
“… 28 Specifically, a prior history of a self-harm presentation appeared to increase the risk of SARS-CoV-2 infection; in contrast, infection was not associated with subsequent self-harm. 28 Emerging evidence suggests that SARS-CoV-2 infection may have a bidirectional relationship with psychiatric illness with each being a risk factor for occurrence of the other. 29 Therefore, it may be that at least some of the observed associations in our review, specifically those that did not control for the presence of mental disorders, may be confounded since people with psychiatric illnesses are at higher risk for both SARS-CoV-2 infection and STBs.…”
Section: Discussionmentioning
confidence: 95%